Pengaruh kemampuan numerik terhadap kemampuan pemecahan masalah matematis - Arrahman, Rahmat; Spriyanti, Nana; Susanto, Andi (Jurnal Pendidikan Matematika RAFA, 2023)
This study aims to determine the effect of numerical ability on mathematical problem solving abilities of students in class XI MAS in Bayur. This research is a quantitative study with total sampling technique. Data were collected through tests and analyzed by simple linear regression. The results showed that numerical ability had a positive effect on mathematical problem solving skills with the regression equation Y = 32.865 + 0.633X. Numerical ability has a significant effect on mathematical problem solving ability based on the significance level of the numerical ability variable is 0.000 which is smaller than 0.05. The relationship between numerical ability and mathematical problem solving ability is positive based on a correlation coefficient of 0.874. The variable of mathematical problem solving ability is influenced by 76.3% by the variable of numerical ability, the remaining 23.7% is influenced by other variables based on the coefficient of determination of 0.763.